Making Waves: Joining forces for better doctoral education in water research. (1st October 2021) - Taka, Maija; Verbrugge, Laura; Varis, Olli
Abstract: We argue that doctoral education in water needs an elevated focus towards educating game changers who can drive innovation and change towards more sustainable futures across academic and non-academic settings. Today's doctoral graduates in water are increasingly employed outside academia, and challenged to understand complex and interconnected systems, to integrate and synthesize information from different disciplines and to lead the way toward increasingly creative, resilient, robust, and socially sustainable solutions. Supervisors are challenged by interdisciplinary research topics and by growing diversity of objectives, too often at the cost of their wellbeing. The need to keep up with the rapid scientific and technological development and floods of big data is pressing. We synthesize key insights from higher education literature and doctoral programs in water research to identify priority actions targeted at four key actor groups: supervisors and supervisees, research group, university, and industry. The actions contribute to appropriate resourcing, enabling an environment for enhanced teamwork practices, and systematic structures for progress. Establishing supporting structures will leverage the much-needed communities of practice involved in co-creating and transforming supervision and education of doctoral students in interdisciplinary water research.